The influence of intrinsic and extrinsic motivation on Malaysian academics participation in the national innovation strategy - Tan, Shen Kian (2016)
The practice of workplace motivation is always use in activating, directing and maintaining people’s behaviors towards specific courses of actions. In this study, the attentions are focus on studying the factors that motivating Malaysia academic citizens in participating in Malaysia National Innovation Strategy. The methodology of this exploratory study involve a quantitative designed, web-based survey method. Population include all academicians with Malaysia citizenships in all twenty Malaysia public universities, while actual samples collected consist of 833 respondents. Results were analyzed by Kruskall-Wallis test (SPSS) and Structural Equation Modelling-Partial Least Square (SmartPLS). Findings has presented that the eight motivation factors of Equity, Trust, Responsibility, Actualization, Physical Condition, Culture, Career Prospect, and Work-Life Integration have different significant results among the three categories of Malaysia public universities. Implication of this study has revealed the significance of motivation factors National Innovation Strategy, as well as the differences of significances among the three categories of public universities.